Numerical and experimental analysis of the Young's modulus of cold compacted powder materials. (September 2017) - Salvadori, A.; Lee, S.; Gillman, A.; Matouš, K.; Shuck, C.; Mukasyan, A.; Beason, M.T.; Gunduz, I.E.; Son, S.F.
Highlights: We present a unique co-designed experimental, theoretical, and numerical investigation of Young's modulus for cold compacted powder materials. The concept of image-based modeling is used to reconstruct the morphology of the powder structure with high fidelity. Analyses on aluminum powder pellets provide significant understanding of the microstructural mechanisms that preside the increase of the elastic properties with compaction. The role of the stress percolation path and its evolution during material densification is highlighted, showing that a unique value of Young's modulus can hardly be established as a function of the volume fraction only. A scaling law between the surface area of the interconnections and the Young's modulus is provided. Abstract: We present co-designed experimental, theoretical, and numerical investigations aiming at estimating the value of the Young's modulus for cold compacted powder materials. The concept of image-based modeling is used to reconstruct the morphology of the powder structure with high fidelity. Analyses on aluminum powder pellets provide significant understanding of the microstructural mechanisms that preside the increase of the elastic properties with compaction. The role of the stress percolation path and its evolution during material densification is highlighted.